Uterine flushing proteome of the tammar wallaby after reactivation from diapause. Issue 5 (November 2016) - Martin, Florine C; Ang, Ching-Seng; Gardner, David K; Renfree, Marilyn B; Shaw, Geoff
Abstract : The marsupial tammar wallaby has the longest period of embryonic diapause of any mammal, up to 11 months, during which there is no cell division or blastocyst growth. Since the blastocyst in diapause is surrounded by acellular coats, the signals that maintain or terminate diapause involve factors that reside in uterine secretions. The nature of such factors remains to be resolved. In this study, uterine flushings (UFs) were used to assess changes in uterine secretions of tammars using liquid chromatography–mass spectrometry (LC–MS/MS) during diapause (day 0 and 3) and reactivation days (d) 4, 5, 6, 8, 9, 11 and 24 after removal of pouch young (RPY), which initiates embryonic development. This study supports earlier suggestions that the presence of specific factors stimulate reactivation, early embryonic growth and cell proliferation. A mitogen, hepatoma-derived growth factor and soluble epidermal growth factor receptors were observed from d3 until at least d11 RPY when these secreted proteins constituted 21% of the UF proteome. Binding of these factors to specific cellular receptors or growth factors may directly stimulate DNA synthesis and division in endometrial gland cells. Proteins involved in the p53/CDKN1A (p21) cell cycle inhibition pathway were also observed in the diapause samples. Progesterone and most of the oestrogen-regulated proteins were present in the UF after d3, which is concomitant with the start of blastocyst mitoses at d4. We propose that once the p21 inhibition of the cell cycle is lost, growth factors including HDGF and EGFR are responsible for reactivation of the diapausing blastocyst via the uterine secretions.